ANALISIS KESESUAIAN PENGGUNAAN LAHAN BERDASARKAN ARAHAN FUNGSI KAWASAN DI DAERAH ALIRAN SUNGAI (DAS) ALO KABUPATEN GORONTALO (Analysis of The Suitability of Land Use Based on The Direction of The Function of The Area in Alo Basin in Gorontalo District) - Ulfan R. Ake; Arthur Gani Koto; Ivan Taslim (Universitas Muhammadiyah Gorontalo, 2018)
Abstract - Determination of the function of the area is very important in order to preserve and prevent environmental damage, so as to improve the safety, prosperity, and comfort of life. The occurrence of landslide in Gorontalo regency partly from alo watershed area in pulubala subdistrict and tibawa sub-district has destroyed 221 houses, 31 houses were badly damaged and 628 people were injured. In addition, the factors causing avalanches in the alo watershed are slope, soil type, high rainfall and community land use. This study aims to: (1) map the main function of the area in alo watershed based on the decree of the minister of agriculture no. 837 / kpts / um / 11/1980 (2) analyze the suitability of land use in the alo watershed based on the main function of the region and present it in the form map. Method and analysis used in this research is scoring, overlay, and field survey. Based on the result of alo river basin analysis, there are 4 directives of the area function. The function of protected area covers 93.09 ha (0.40%), buffer area 4970.74 ha (21.13), annual cultivation area 3614.56 ha (15.37%), while the cultivation area annual crops and settlements have an area of 14,843.3 ha (63.10%). Most of the land use in the alo basin is said to be appropriate to the direction of the function of the area, where the land has an area of 18,566.6 hectares or 79.05% while the unsuitable land is 4,920.7 ha or 20.95% of the entire alo watershed. Keywords: land suitability, directed land functions, alo watershed, gorontalo Abstrak - Penetapan fungsi kawasan sangat penting guna menjaga kelestarian dan mencegah kerusakan lingkungan, sehingga dapat meningkatan keselamatan, kesejahteraan serta kenyamanan hidup. Kejadian longsor di Kabupaten Gorontalo sebagian dari wilayah DAS Alo yaitu berada di Kecamatan Pulubala dan Kecamatan Tibawa telah menghancurkan 221 buah rumah, 31 buah rumah di antaranya rusak parah, dan korban luka-luka sejumlah 628 orang. Selain itu yang menjadi faktor penyebab longsoran di DAS Alo diantaranya adalah faktor lereng, jenis tanah, curah hujan yang tinggi dan pemanfaatan lahan oleh masyarakat. Penelitian ini bertujuan untuk: (1) Memetakan arahan fungsi utama kawasan di DAS Alo berdasarkan Surat Keputusan Menteri Pertanian Nomor 837/Kpts/Um/11/1980 (2) Menganalisis kesesuaian penggunaan lahan di DAS Alo berdasarkan arahan fungsi utama kawasan dan menyajikannya dalam bentuk peta. Metode dan analisis yang digunakan dalam penelitian ini adalah skoring, overlay, dan survey lapangan. Berdasarkan hasil analisis DAS Alo memiliki 4 arahan fungsi kawasan yaitu Arahan fungsi kawasan lindung memilki luas 93.09 ha (0.40%), kawasan penyangga 4970.74 ha (21.13), kawasan budidaya tanaman tahunan 3614,56 ha (15,37%), sedangkan kawasan budidaya tanaman semusim dan pemukiman memilki luas sebasar 14.843,3 ha (63,10%). Sebagian besar pemanfaatan lahan di DAS Alo dikatakan sudah sesuai terhadap arahan fungsi kawasan, dimana lahan sesuai memilki luas 18.566,6 ha atau 79,05 % sedangkan lahan yang tidak sesuai 4.920,7 ha atau 20,95 % dari seluruh wilayah DAS Alo. Kata kunci: kesesuaian lahan, arahan fungsi lahan, daerah aliran sungai alo, gorontalo